OK Computer: Analogue Death, Digital Rebirth, and Radiohead’s Electronic Turn - Kwasu David Tembo (Revue LISA)
OK Computer marks an important volta or fin-de-siècle in Radiohead’s oeuvre. It is clear that the thematic leitmotif running throughout the album, influencing everything from Yorke’s lyrics, the sonic dynamism and experimentation on show, to the album’s artwork, is, in a word, denouement. This paper will explore the theme of denouement in relation to the album’s sonic, thematic, and aesthetic qualities. It will argue that the album’s title refers to the acquiescence, acceptance, and transition from more traditional analogue methods of making, recording, and distributing music adopted by the band up to and including The Bends (1995), and an inauguration of the band’s conscientious pursuit of radical digital experimentation to follow in Kid A (2000). In order to provide as holistic an analysis of the theme of denouement as possible, this paper’s analysis will be predicated on questions, concepts, and ideas including but not limited to the following: the leitmotif of denouement present in the thematic influences on the album, such as the influence of the track “Exit Music (For a Film)” commissioned by director Baz Luhrmann on the rest of the album; the influence of radical analogue experimentation culled from Miles Davis’ avant-garde jazz fusion album Bitches Brew (1970); the theme of resignation, interstice, liminality, and transference/-formation in relation to the “computer syndrome” as discussed in Michael Heffernan’s “Fin de Siècle, Fin du Monde?” (2000). The goal of this paper is to explore how OK Computer simultaneously represents Radiohead’s analogue death, digital rebirth, and embracing of the computer.